The Potential Prognostic, Diagnostic and Therapeutic Targets for Recurrent Arrhythmias in Patients with Coronary Restenosis and Reocclusions After Coronary Stenting - Li, Xia; Guo, Dianxuan; Zhou, Wenhang; Hu, Youdong; Zhou, Hualan; Chen, Ying (Current Pharmaceutical Design, 2022)
Background: The interplay of oxidative stress, proinflammatory microparticles, and proinflammatory cytokines in recurrent arrhythmias is unknown in elderly patients with coronary restenosis and reocclusions after coronary stenting. Objective: This research sought to investigate the potential diagnostic and therapeutic targets for recurrent arrhythmias in patients with coronary restenosis and reocclusions after coronary stenting. Methods: We examined whether oxidative stress, proinflammatory microparticles, and proinflammatory cytokines could have effects that lead to recurrent arrhythmias in elderly patients with coronary restenosis and reocclusions. We measured the levels of malondialdehyde (MDA), CD31 + endothelial microparticle (CD31 EMP), CD62E + endothelial microparticle (CD62E + EMP), high-sensitivity C-reactive protein (hs-CRP), interleukin- 1β (IL-1β), interleukin-6 (IL-6), interleukin-8 (IL-8) and tumor necrosis factor-α (TNF-α), as well as oxidized low-density lipoprotein (OX-LDL), and assessed the effects of relationship between oxidative stress, proinflammatory microparticles, and proinflammatory cytokines on recurrent atrial and ventricular arrhythmias in elderly patients with coronary restenosis and reocclusions after coronary stenting. Results: The levels of CD31 + EMP, CD62E + EMP, MDA, hs-CRP, IL-1β, IL-6, IL-8, TNF-α and OX-LDL were found to be increased significantly in coronary restenosis + recurrent atrial arrhythmia group compared to without coronary restenosis and coronary restenosis + without recurrent atrial arrhythmia groups, respectively (P < 0.001). Patients in the coronary reocclusion + recurrent ventricular arrhythmia group also exhibited significantly increased levels of CD31 + EMP, CD62E + EMP, MDA, hs-CRP, IL-1β, IL-6, IL-8, TNF-α and OXLDL compared to without coronary reocclusion and coronary reocclusion + without recurrent ventricular arrhythmia groups, respectively (P < 0.001). Conclusion: Proinflammatory microparticles, proinflammatory cytokines, and oxidative stress might act as potential targets for recurrent arrhythmias in patients with coronary restenosis and reocclusions after coronary stenting.
Keywords: Coronary stenting